The Communication Skill on the Performance of Internal Auditors in Thailand Public Limited Company - Narkchai, Sutana; Fadzil, Faudziah Hanim Binti (International Review of Management and Marketing, 2017)
The issue of performance of internal auditors is important since Thailand was also affected by the accounting scandals. The expanded scope in the definition of internal auditing and new regulatory requirements such as the Sarbanes-Oxley Act 2002 has increased the demands on the internal auditing. This study was conducted to examine the factors that influence the communication skills on the performance of internal auditors in Thailand public limited companies. To achieve this objective, the hypothesis was formulated based on previous studies and the agency theory. Survey questionnaires were sent to the Chief Audit Executives (CAEs) to determine their effectiveness on their performance based on the professional standards issued by the IPPF (2017) indicators. A total of 520 questionnaires were distributed, but only 146 were usable. Multiple regression was used to test the relationship between the variables. The existence of communication skills and performance of internal auditors is needed to strengthen the internal audit effectiveness between internal auditors and auditees. This study serves as an important catalyst for further research and discussion in this area. More importantly, there is lack of research in Thailand concerning the relationship between internal audit functions with the performance of internal auditors. Keywords: performance of internal auditors, communication skill, IPPF, Thailand Public Limited Company, IIA. JEL Classifications: L1, M42